2007
DOI: 10.1002/lt.21104
|View full text |Cite
|
Sign up to set email alerts
|

MELD is superior to King's college and Clichy's criteria to assess prognosis in fulminant hepatic failure

Abstract: Assessment of prognosis in fulminant hepatic failure (FHF) is essential for the need and appropriate timing of orthotopic liver transplantation (OLT). In this study we investigated the prognostic efficacy of King's College criteria, Clichy's criteria, Model for End-Stage Liver Disease (MELD), and Pediatric End-Stage Liver Disease (PELD) in 120 consecutive patients with FHF. Survival with medical therapy (18%), death without OLT (15%), and receipt of a liver transplant were similar in adults (n ϭ 64) and childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
124
5
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(138 citation statements)
references
References 30 publications
(39 reference statements)
5
124
5
4
Order By: Relevance
“…3 In fact, lactate alone at 12 hours had similar performance to SOFA and better performance than King's criteria (AUC: 0.76, 0.79, and 0.65, respectively). 3 Importantly, the negative predictive value (NPV), which is low in many prognostic scores in FHF, as acknowledge by Yantorno et al 2 in their discussion, was higher for lactate at 12 hours (NPV: 0.73), compared to the NPV of the King's criteria (NPV: 0.65) in our study, 3 and to the NPVs of the new prognostic score and MELD score (NPV: 0.65 and 0.61, respectively) in the study by Dhiman et al 1 Thus, we believe that further studies are needed to assess the prognostic accuracy of any new markers both early in the course of FHF and serially, as Dr. O'Grady 9 emphasized in the editorial accompanying the Dhiman et al 1 article. This should lead to better prognostication at different time points during the evolution of the FHF.…”
mentioning
confidence: 99%
“…3 In fact, lactate alone at 12 hours had similar performance to SOFA and better performance than King's criteria (AUC: 0.76, 0.79, and 0.65, respectively). 3 Importantly, the negative predictive value (NPV), which is low in many prognostic scores in FHF, as acknowledge by Yantorno et al 2 in their discussion, was higher for lactate at 12 hours (NPV: 0.73), compared to the NPV of the King's criteria (NPV: 0.65) in our study, 3 and to the NPVs of the new prognostic score and MELD score (NPV: 0.65 and 0.61, respectively) in the study by Dhiman et al 1 Thus, we believe that further studies are needed to assess the prognostic accuracy of any new markers both early in the course of FHF and serially, as Dr. O'Grady 9 emphasized in the editorial accompanying the Dhiman et al 1 article. This should lead to better prognostication at different time points during the evolution of the FHF.…”
mentioning
confidence: 99%
“…Patients from the study of Dhiman et al 2 exclusively had a viral etiology for FHF, whereas patients from the other study 1 had multifactorial causes. The etiology of FHF might be important because the King's College criteria have proposed different predictive variables for FHF with respect to the use or nonuse of acetaminophen.…”
mentioning
confidence: 96%
“…1,2 The two studies by Yantorno et al 1 from Argentina and Dhiman et al 2 from India investigated the prognostic ability of the Model for End-Stage Liver Disease (MELD), King's College, and Clichy criteria for predicting the mortality in patients with fulminant hepatic failure (FHF). Yantorno et al reported that MELD is the best prognostic model among the three, whereas Dhiman et al found that a combination of the parameters (clinical prognostic indicators) from these models is more accurate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MELD has also been shown to have utility in predicting outcome in patients suffering from acute liver failure, alcoholic hepatitis, and in patients with chronic liver disease undergoing surgery or experiencing traumatic injury [14][15][16][17][18]. To date, however, it has not been shown to reliably predict post-liver transplant mortality.…”
mentioning
confidence: 99%